ETIOLOGY OF MALE INFERTILITY IN JAKARTA - Basukarno, Ari; Birowo, Ponco; Rasyid, Nur (Indonesian Urological Association, 2016)
Objective: The etiology and risk factors of male infertility in huge Indonesian population has not yet been defined. This study was aim to evaluate the distribution and pattern of male infertility in Jakarta. Material & Methods: Retrospective study of Infertility database of Cipto Mangunkusumo Referral Hospital Jakarta, Bunda Hospital Jakarta, and ASRI Hospital Jakarta from 2005 until 2015 were analyzed using SPSS ver. 20. Patients’ characteristic and demography were stated. Results: There were 1062 patients with most of them suffered from primary infertility of their first time-marriage. Average age of husband, wife, and duration of marriage were 36.63± 7.10, 32.32 ± 4.92, and 5.7 ± 4.18 years old respectively. Smoking habit was recorded in 25% of patients while exposure and occupational hazard were only found in less than 2% of them. Coital problems occured in 17% of patients with 30% of them did not have routine sexual intercourse per week. Physical examination revealed that more than 70% of them had varicocele while USG Doppler of scrotum found varicocele in less than 50%. Only 5.13% of patients had normal sperm analysis, mostly azoospermia. Hormonal abnormality occured in more than 30% patients, varied in testosterone, FSH, and LH level.Conclusion: Male infertility was mostly caused by abnormal sperm characteristics followed by abnormal hormonal analysis. Exposure and occupational hazard did not play a big role in male infertility. Future study in risk factors of abnormal sperm characteristics could be done.